2011
DOI: 10.1186/1297-9716-42-118
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced Salmonella Typhimurium recrudescence in pigs coincides with cortisol induced increased intracellular proliferation in macrophages

Abstract: Salmonella Typhimurium infections in pigs often result in the development of carriers that intermittently excrete Salmonella in very low numbers. During periods of stress, for example transport to the slaughterhouse, recrudescence of Salmonella may occur, but the mechanism of this stress related recrudescence is poorly understood. Therefore, the aim of the present study was to determine the role of the stress hormone cortisol in Salmonella recrudescence by pigs. We showed that a 24 h feed withdrawal increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 46 publications
3
56
0
2
Order By: Relevance
“…Researches indicated that CORT increased the proliferation of Salmonella in primary porcine alveolar macrophages [21]. Hosoda et al [22] revealed that estradiol and progesterone inhibited the growth of Helicobacter pylori in vitro culture [22].…”
Section: Discussionmentioning
confidence: 99%
“…Researches indicated that CORT increased the proliferation of Salmonella in primary porcine alveolar macrophages [21]. Hosoda et al [22] revealed that estradiol and progesterone inhibited the growth of Helicobacter pylori in vitro culture [22].…”
Section: Discussionmentioning
confidence: 99%
“…Stress is associated with a recrudescence of the infection (71,95). Handling, loading, mixing with unfamil iar pigs, high stocking densities, and changes in environ ment, including temperature, are some of the associated factors that promote stress.…”
Section: Salmonella At Slaughter In Swine Production: Influencing Facmentioning
confidence: 99%
“…Once a pig is infected with Salmonella, it will carry and shed Salmonella intermittently at low numbers throughout its life (Verbrugghe et al, 2011). Under stressful conditions, such as transportation and mixing of novel pigs (Callaway et al, 2006), pigs can resume fecal shedding and cross-contaminate pigs at lairage just before slaughter (Hurd et al, 2001), thus resulting in a higher prevalence of contaminated carcasses (Verbrugghe et al, 2011). The risk factors associated with Salmonella infection have been related to the size of the herds, the presence of birds within the barn, and the type of feeding (García-Feliz et al, 2009), but when implementing a comprehensive FIG.…”
Section: Discussionmentioning
confidence: 99%